STRATEGI MANAJEMEN NYERI BERKORELASI DENGAN INTENSITAS NYERI PADA PASIEN POST OPERASI FRAKTUR EKTREMITAS BAWAH - Nurhayati Nurhayati; Lathifah Hanum; Nadilla Aprilya Saphira (Poltekkes Kemenkes Aceh, 2023)
Surgery can cause very severe pain in patients due to surgical incisions. To treat pain in fracture patients, effective pain management is needed. The pain management provided must be able to meet the patient's needs, one of which is the need for comfort. namely pharmacology and non-pharmacology. This study aims to identify the relationship between pain intensity and pain management strategies in post lower extremity fracture patients. This research is quantitative analytic in nature with a cross sectional approach. The sampling technique used purposive sampling with a total sample of 43 postoperative lower extremity fracture respondents. The instrument in this study used a pain scale for pain intensity, while the pain management strategy used the American pain society patient outcome questionnaire revised, with interview collection techniques. The results of the study showed that there was a relationship between pain intensity and pain management strategies in postoperative lower extremity fracture patients. 15 people (60.0%) experienced severe pain with good pain management strategies, 10 people (40.0%) had severe pain with sufficient pain management strategies, while 17 people had moderate pain with good pain management strategies (94.4%), and moderate pain with sufficient pain management strategies in 1 person (5.6%). This is based on the results of the calculation of the chi-square statistical test obtained Pvalue = 0.014 <α = 0.05. There is a relationship between pain intensity felt by patients with pain management strategies in postoperative lower extremity fracture patients at Meuraxa Hospital Banda Aceh.